FORMATION OF GERMINATION OF CORN SEEDS - Stiurko , М. (Bulletin of Lviv National Environmental University. Series Agronomy, 2024)
Growing corn is crucially important to Ukraine's grain industry. Corn is a versatile and highly productive crop. Ukraine has the potential for stable grain production, particularly in the Western Forest Steppe region. High-quality seed material is essential for high yields, with germination being a key indicator of seed quality. Factors such as moisture dynamics, dry matter accumulation, and seed humidity during harvesting – all affect germination. Research was conducted on corn hybrids of Ukrainian selection with different maturity groups, namely Dniprovskyi 181 SV (early ripe), Kremin 200 SV (mid-early), Liubava 279 MV (mid-early), Rozivskyi 311 SV (mid-ripe). During the research, features of the ripening of corn hybrids were established and the humidity at which seed germination was formed was determined.The research on Ukrainian corn hybrids with different maturity groups indicated that seeds contain 71–83 % of the maximum dry matter at a moisture content of 50–51 %. The maximum dry matter content was found at a humidity of 30–33 %. Laboratory germination was achieved at a humidity of 47–53 % and below, depending on the hybrids. It is established that the moisture yield of seeds has increased significantly and is 0.8–2.3 % per day, depending on the hybrids, which is higher compared to long-term data. The optimal field germination and productivity were achieved at a moisture content of 32–40 %, depending on the maturity group of the hybrids. It is recommended to harvest corn hybrid seeds at a moisture content of 40 %, when seed quality indicators have been already formed. Post-harvest processing should bring the seeds to conditioned moisture levels to maintain their quality.